Which factors modulate spontaneous motor tempo? A systematic review of the literature - Desbernats, Anaïs; Martin, Elodie; Tallet, Jessica (Frontiers in Psychology, 2023)
Intentionally or not, humans produce rhythmic behaviors (e.g. walking, speaking, clapping). In 1974, Paul Fraisse defined rhythm as "periodic movement which obeys a temporal program specific to the subject and which depends little on the conditions of the action" (Fraisse, 1974, p 47). Among spontaneous rhythms, the Spontaneous Motor Tempo (SMT) corresponds to the tempo at which someone produces movements in the absence of stimuli at the most regular, natural and pleasant rhythm for him/her. Fraisse (1974) pointed large differences in SMT at an inter-individual level but low differences at intra-individual level. Even if several factors have been suggested to influence the SMT (e.g., the age of participants), we do not know yet which factors actually modulate the value of the SMT. In this context, the objectives of the present systematic review are to characterize the range of SMT values found in the literature in healthy human adults, and to identify all the factors modulating SMT in humans. Our results highlight that (1) the SMT value of 600 ms is far from being a common value in healthy adults and (2) many factors modulate the SMT. We discuss our results in terms of intrinsic factors -in relation to personal characteristics -and extrinsic factors -in relation to environmental characteristics. Recommendations are proposed to assess the SMT in future research, and in rehabilitative, educative and sport interventions involving rhythmic behaviors.